Financial statement fraud in Europe - Campos, Joana Filipa Almeida (2020)
In recent years, more and more fraud cases have been detected in large companies, which undermined the confidence of the markets. However, although this is a reality, the study of the subject in Europe continues to be quite scarce. Therefore, despite an increase in regulatory capacity, a greater focus on the subject in recent years and a growing awareness of the effects of this type of action, there are still few effective prevention tools at the community level. In addition, there are few guiding traits for agents with a central role not in their identification but prevention, the financial auditors. The purpose of this dissertation is to fill this gap in the research on fraud in Europe. Through the study of cases of accounting fraud duly identified by the various European agencies for having incurred in misleading accounting, the indicators that best explain the fraud event in Europe were identified, reaching a total explained variance of 90.5%. In sum, the identified indicators are financial ratios such as the proportion of firm liabilities to total assets, a measure of the days that the entity needs to meet its debts with third parties, a measure of changes in net income, and the size of the auditor firm. Thus, the most significant variables that explain the phenomenon of Financial Statement Fraud in Europe are measures of financial leverage, performance, and financial risk